2011
DOI: 10.1007/s10353-011-0003-5
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of outcomes after open and laparoscopic Nissen's fundoplication in the treatment for gastro-oesophageal reflux disease

Abstract: Background: A meta-analysis of published literature comparing peri-operative, short-term and longterm outcomes after open Nissen's fundoplication (ONF) versus laparoscopic Nissen fundoplication (LNF) for gastro-oesophageal reflux disease.Methods: Electronic databases were searched from January 1991 to October 2009. A systematic review was performed to obtain a summative outcome.Results: Nine randomized controlled trials involving 657 patients were analysed. Three hundred and thirty-six patients were in the lap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
(121 reference statements)
0
8
0
Order By: Relevance
“…2 therapy, effective antireflux surgery eliminates acid and bile reflux and normalizes bile acid, which induces tissue stress, and mediates the regression of Barrett's esophagus. [2][3][4] In line with this notion, effective fundoplication potentiates the success of radiofrequency ablation of Barrett's esophagus. 5 Perhaps the data of the present study will serve as the basis for the development of a new anti-Barrett's esophagus drug.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…2 therapy, effective antireflux surgery eliminates acid and bile reflux and normalizes bile acid, which induces tissue stress, and mediates the regression of Barrett's esophagus. [2][3][4] In line with this notion, effective fundoplication potentiates the success of radiofrequency ablation of Barrett's esophagus. 5 Perhaps the data of the present study will serve as the basis for the development of a new anti-Barrett's esophagus drug.…”
Section: To the Editormentioning
confidence: 99%
“…At present, the combination of radiofrequency ablation and effective antireflux surgery represents promising treatment options for the effective and durable eradication of Barrett's esophagus. [2][3][4][5] Future studies will have to elucidate, if the early implementation of less invasive antireflux procedures (ie, laparoscopic sphincter augmentation) before the reflux-induced inactivation of the normal genetic program will contribute to prevent the development of Barrett's esophagus and esophageal adenocarcinoma. 6,7 The authors are to be congratulated for this outstanding work and kindly asked to address the above considerations.…”
Section: To the Editormentioning
confidence: 99%
“…Thus, by theory, the removal of Barrett’s tissue and the elimination of reflux should contribute to cancer prevention. Going in line with with this notion, recent studies found that elimination of reflux by effective antireflux surgery contributes to increase the yield of radiofrequency ablation to eradicate Barrett’s esophagus , when compared to ablation and post-ablational proton pump inhibitor (PPI) therapy, which solely changes the pH of the reflux, but not the reflux per se [3,5]. …”
mentioning
confidence: 99%
“…Therefore a risk profile- (anamnestic, demographic & endoscopic, esophageal function tests characteristics) [3] and endoscopically visualized genetic profile- based tailored management of Barrett’s esophagus for cancer prevention may be realistic in the future [1,4,6,7]. Thus, Barrett’s positive individuals with increased reflux due to severely impaired function of the esophagus may be offered elimination of acid and bile reflux by an effective anti reflux surgery prior to ablation [3,5]. In contrast, ablation and subsequent PPI therapy seems reasonable for those with Barrett’s esophagus and normal esophageal function and reflux monitoring [3].…”
mentioning
confidence: 99%
“…CLO may have progressed from CM to IM because of an inefficient fundoplication. [2][3][4]6 On proton pump inhibitor therapy, a progression from CM to IM was observed in more than 50% of the cases. 1,7 Taken together, the present data enlarge our understanding regarding the natural history of columnar lined oesophagus and should motivate the initiation of larger studies to more accurately define the risk factors for intestinal metaplasia/cancer progression among persons with cardiac mucosa/oxyntocardiac mucosa (i.e.…”
mentioning
confidence: 99%